2011
DOI: 10.1002/ceat.201000373
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Liquid Hydrodynamics and Mass Transfer in Aqueous Alcohol Solutions in a Split‐Cylinder Airlift Reactor

Abstract: The influences of aliphatic alcohols (C n H 2n+1 OH, n = 1-4) and their concentrations (0-1 vol.-%) on gas holdup, liquid circulation velocity, mixing time, and overall volumetric gas-liquid oxygen mass transfer coefficient were considered in a split-cylinder airlift reactor sparged with air. The carbon chain length of the alcohols and their concentration affect the airlift reactor performance. Alcohols reduced the average bubble sizes and increased the gas holdup, the interfacial area for mass transfer, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…The split-cylinder airlift reactor used in this research was the same as the applied apparatus by Moraveji et al (2011). All the experiments were carried out in ambient conditions (atmospheric pressure and 25 ± 0.5 • C).…”
Section: Apparatus Setup and Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The split-cylinder airlift reactor used in this research was the same as the applied apparatus by Moraveji et al (2011). All the experiments were carried out in ambient conditions (atmospheric pressure and 25 ± 0.5 • C).…”
Section: Apparatus Setup and Measurement Methodsmentioning
confidence: 99%
“…All the experiments were carried out in ambient conditions (atmospheric pressure and 25 ± 0.5 • C). Gas holdup, liquid circulating velocity, and oxygen mass transfer coefficient measurement methods have been reported in the literature (Moraveji et al, 2011). Zuber and Findlay's method (1965)I was used to find the flow regimes as well.…”
Section: Apparatus Setup and Measurement Methodsmentioning
confidence: 99%
“…The split-cylinder airlift reactor used in this research was the same as the apparatus applied by Moraveji et al (2011b), as shown in Figure 1 The maximum possible porosity of the packing is equal to 78.0%. As is known, packing normally increases the mass transfer and gas hold-up.…”
Section: Apparatus Set Up and Measurement Methodsmentioning
confidence: 99%
“…In this study, the volume expansion method was applied to measure the overall gas hold-up (ε) during the steady state condition in the airlift bioreactor. Liquid circulation velocity (U L ) and oxygen mass transfer coefficient measurement methods have been proposed and reviewed elsewhere (Moraveji et al, 2011b).…”
Section: Apparatus Set Up and Measurement Methodsmentioning
confidence: 99%
“…1 This wide application of airli reactors is due to their advantages including low operation and maintenance cost and high mass transfer rate. 3 Oil-in-water micro-emulsions are one of the main wastes of oil renery, chemical and petrochemical companies. Air is sparged through the riser which makes the uid ow upward in the riser and downward in the down-comer.…”
Section: Introductionmentioning
confidence: 99%